Uncovering the Genetic Architecture of Fruiting Efficiency in Bread Wheat: A Viable Alternative to Increase Yield Potential. Issue 5 (5th September 2019) - Gerard, Guillermo Sebastián; Alqudah, Ahmad; Lohwasser, Ulrike; Börner, Andreas; Simón, María Rosa
Abstract : To meet the estimated future increase in wheat ( Triticum aestivum L.) demand, exploring and dissecting the genetic basis of yield‐related traits play a crucial role in wheat yield improvement. In this study, we evaluated 12 grain yield‐related traits including fruiting efficiency (FE) in a wheat panel through genome‐wide association mapping (GWAS) approach. The panel displayed large phenotypic variation for all the measured traits, FE was positively associated with grain number per spike but not related to thousand kernel weight. Interestingly, FE was mostly explained by grain number per fertile spikelet (GFS), whereas the latter was determined by spikelet weight (SW). The GWAS identified 44 significant marker‐trait associations (MTAs) across almost the entire wheat genome linked to the 12 yield‐related traits, including four MTAs on chromosomes 2A, 2D, 4D, and 5A associated with FE. Several significant markers were identified in genomic regions previously reported, whereas others appeared to be potentially novel loci. Particularly, the co‐location of significant markers for yield‐related traits with major genes underlying plant development showed pleiotropic effects and the key role of these genes in modulating agronomic traits. The markers linked to FE, GFS, and SW are promising, especially considering that due to the destructive phenotypic determination, their improvement in early breeding generations can only be made by marker‐assisted selection. Taken together, these findings are encouraging and suggest the potential value of FE and associated traits as possible selection criteria to increase yield potential in wheat breeding programs.